(untitled) (Research, Society and Development, 2024)
Objective: This study aims to develop and validate a score to identify the level of pharmaceutical care that will be provided to patients hospitalized in a tertiary hospital in Salvador, Bahia. Method: The present study took place over a period of one year (2022-2023) at reference hospital in Salvador. An online form was constructed containing several variables collected from the literature, which were later validated by the Delphi-Method. The evaluation of the experts occurred in two stages mediated by the Likert scale until reaching a consensus and finalizing the score. Finally, a pilot test was conducted to evaluate the agreement in the applicability of this score, based on the responses of a group of pharmacists using the weighted Kappa Cohen. Result: The pharmaceutical risk score was developed from the decisions of the specialists, considering eight variables such as the number of medications, age, comorbidities, and others capable of assessing the level of care that hospitalized patients demand, being responsible for assisting the pharmaceutical clinical practice. The model presented a weighted Kappa Cohen of 0.67 (p-value <0.0001; CI 0.46-0.87), demonstrating moderate and satisfactory reliability. Thus, the score allows the pharmacist to offer proportional attention to the needs of the patient, performing their activities more safely. Conclusion: This study developed an objective and clear risk assessment instrument from the pharmaceutical perspective, based on evidence in the literature. The implementation of this score will significantly improve pharmaceutical care, enabling pharmacists to offer proportional attention to patient needs and conduct their activities more safely.